A Method for Seeking Low-Redundancy Large Linear Arrays in Aperture Synthesis Microwave Radiometers - Dong, Jian; Li, Qingxia; Jin, Rong; Zhu, Yaoting; Huang, Quanliang; Gui, Liangqi (IEEE transactions on antennas and propagation, 2010)
For one-dimensional aperture synthesis microwave radiometers, the optimal placement of antenna elements in a low-redundancy linear array (LRLA) is difficult when large numbers of elements are involved. In this paper, the general structure of large LRLAs is summarized first, and then a novel stochastic optimization technique, ant colony optimization (ACO), is applied to the search for low redundancy arrays. By combining the general structure with the ACO procedure, an efficient method is proposed for a rapid exploration for optimal array configurations. Numerical studies show that the method can generate various large LRLAs with lower redundancy than the previous algorithms did and the computational cost is greatly reduced. Based on the method, several analytical patterns for LRLAs are further derived, which can yield various array configurations with very low redundancy in nearly zero computation time. Both the method and the resulting configurations can be utilized to facilitate antenna array design in synthetic aperture radiometers with high spatial resolution.